New amide derivatives of quinoxaline 1,4-di-N-oxide with leishmanicidal and antiplasmodial activities (2013)
ABSTARCT: Malaria and leishmaniasis are two of the World’s most important tropical parasitic diseases. Continuing with our efforts to identify new compounds active against malaria and leishmaniasis, twelve new 1,4-di-N-oxide quinoxaline derivatives were synthesized and evaluated for their in vitro antimalarial and antileishmanial activity against Plasmodium falciparum FCR-3 strain, Leishmania infantum and Leishmania amazonensis. Their toxicity against VERO cells (normal monkey kidney cells) was also assessed. The results obtained indicate that a cyclopentyl derivative had the best antiplasmodial activity (2.9 µM), while a cyclohexyl derivative (2.5 µM) showed the best activity against L. amazonensis, and a 3-chloropropyl derivative (0.7 µM) showed the best results against L. infantum. All these compounds also have a Cl substituent in the R7 position